“Who Champions or Mentors Others”? The Role of Personal Resources in the Perceived Organizational Politics and Job Attitudes Relationship - Khan, Hira Salah ud din; Siddiqui, Shakira Huma; Zhiqiang, Ma; Weijun, Hu; Mingxing, Li (Frontiers in Psychology, 2021)
Drawing insight from affective events theory, this study presents a new dimension of perceived organizational politics and job attitudes. The motivation for this study was based on the fact that perceived organizational politics affect job attitudes and that personal resources (political skill and work ethic) moderate the direct relationship between perceived organizational politics and job attitudes in the context of the higher education sector. In this regard, the data was collected through purposive sampling from 310 faculty members from higher education institutions in Pakistan. To test the relationships among the variables we employed structural equation modeling via the AMOS software version 24.0. The results indicated that perceived organizational politics were significantly negatively related to job satisfaction. Moreover, perceived organizational politics were non-significantly related to job involvement. Political skills and work ethic weakened the relationship between perceived organizational politics and job satisfaction. Few investigations have been done on how personal resources (Political Skill and work ethic) affect the relationship between perceived organizational politics and job attitudes. We anticipated that these personal resources could mitigate the negative effect of perceived organizational politics and job attitudes. This study also suggests organizations to train their employees to develop essential personal skills.